2019
DOI: 10.1155/2019/2489584
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stem Cell Transplantation Attenuates Inflammation and Promotes Liver Regeneration after Ischemia-Reperfusion and Hemihepatectomy in Swine

Abstract: Aim To study the anti-inflammatory and liver regenerative effects of adipose-derived mesenchymal stem cells (ADSCs) on a porcine model of ischemia-reperfusion (IR) and hemihepatectomy. Methods Eighteen healthy Bama miniature pigs were randomly divided into the sham-operated (sham), untreated IR injury (IRI), and ADSC-transplanted (ADSC) groups. Hepatic IR was established by laparoscopic hemihepatectomy. ADSCs were transplanted directly into the liver parenchyma after the surgery. Hepatic inflammation and liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…The Mesenchymal and Tissue Stem Cell Committee of the International Cell Therapy Association has proposed a minimum defined standard for characterizing human MSCs (Pittenger et al, 1999;Dominici et al, 2006), including adhesion to plastic, multi-directional differentiation ability and expression of distinct surface markers. The ADSCs extracted from the subcutaneous fat of pigs differentiate into osteogenic, adipogenic and hepatic cells, and express CD44, CD29, and CD90 but not CD34 (Brückner et al, 2013;Jiao et al, 2019). Based on these criteria, we successfully isolated and expanded porcine ADSCs in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The Mesenchymal and Tissue Stem Cell Committee of the International Cell Therapy Association has proposed a minimum defined standard for characterizing human MSCs (Pittenger et al, 1999;Dominici et al, 2006), including adhesion to plastic, multi-directional differentiation ability and expression of distinct surface markers. The ADSCs extracted from the subcutaneous fat of pigs differentiate into osteogenic, adipogenic and hepatic cells, and express CD44, CD29, and CD90 but not CD34 (Brückner et al, 2013;Jiao et al, 2019). Based on these criteria, we successfully isolated and expanded porcine ADSCs in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ADSC treatment led to a marked decline in the levels of adverse hematological indicators, such as aspartate aminotransferase (AST), alanine aminotransferase (ALT), total bilirubin (T-BIL), and lactate dehydrogenase (LDH). A different study reported that ADSCs suppressed the level of inflammatory cytokines such as IL-1 β , IL-6, and TNF, while enhancing the secretion of the anti-inflammatory factor IL-10 and the regenerative factors HGF and cyclin D1, thereby ameliorating the IRI-induced damage [ 152 ]. Similar hepatoprotective effects were also found in other trials [ 153 ].…”
Section: Regenerative Medicine Based On Adscsmentioning
confidence: 99%
“…Furthermore, preclinical studies involving injection of ASCs into cardiac muscle in rats [ 53 , 54 ] and pig liver [ 55 ] reported no inflammatory reaction or fibrosis at the injection sites, and similar results were reported when ASCs were systemically injected: The cells were detectable in inflammatory tissues and appeared to play a role in reducing inflammation [ 56 , 57 ]. Nevertheless, in human medicine, it is very important to limit the risks of triggering an immune response.…”
Section: Discussionmentioning
confidence: 73%